Overburden and surface subsidence with slicing paste filling mining in thick coal seams - Zheng, Qiushuang; Wang, Changfeng; Pang, Lifu (Frontiers in Earth Science, 2023)
Abstract: For the problems of overburden failure and surface subsidence caused by the slicing mining of extra-thick coal seams, the paste is generally used for slicing filling. In this paper, a continuous curved beam mechanical model of paste filling mining was established by theoretical analysis with the background of 3305 working face of Yangcheng coal mine, the main controlling factors of surface subsidence were analyzed by using orthogonal experiment and ANP coupled comprehensive assignment,and the vertical displacement distribution of overlying rock under different filling intensity was simulated with the help of numerical simulation software FLAC3D. The results show that: (1)The elastic modulus of the backfill is the main controlling factor. (2)The larger the elastic modulus of the filling body is, the more effective it is in carrying the overburden load, and effectively reduces the maximum surface subsidence.(3)The distance from the mining open-off cut also reflects the amount of surface sinking, with the amount of subsidence rising as the distance from the mining operation rises.